Unconventional magnetic oscillations in a kagome Mott insulator - Guoxin Zheng; Yuan Zhu; Kuan-Wen Chen; Byungmin Kang; Dechen Zhang; Kaila Jenkins; Aaron Chan; Zhenyuan Zeng; Aini Xu; Oscar A. Valenzuela; Joanna Blawat; John Singleton; et al. (Proceedings of the National Academy of Sciences, 2025)
In metals, electrons in a magnetic field undergo cyclotron motion, leading to oscillations in physical properties called quantum oscillations. This phenomenon has never been seen in a robust insulator because there are no mobile electrons. We report an exception to this rule. We study a Mott insulator on a kagome lattice which does not order magnetically down to milli-Kelvin temperatures despite antiferromagnetic interactions. We observe a plateau at magnetization equal to 1 9 Bohr magneton per magnetic ion, accompanied by oscillations in the magnetic torque, reminiscent of quantum oscillations in metals. The temperature dependence obeys Fermi distribution. These phenomena are consistent with a quantum spin liquid state whose excitations are fermionic spinons with a Dirac-like spectrum coupled to an emergent gauge field.